Upaya Meningkatkan Penguasaan Konsep Fisika Materi Usaha dan Energi Menggunakan Media PhET Simulation (Penelitian Tindakan Kelas di Kelas X) - Putri Nabila Hudaimi; Musyarrofah; Umamah; Pu’adi; Suprianto (Mataram University, 2026)
This Classroom Action Research (CAR) aims to improve the mastery of physics concepts of Work and Energy material for class XH students through the Discovery Learning model assisted by PhET Simulation media. The main problem in this study is the low mastery of concepts due to conventional learning and limited physical laboratory facilities. Through three cycles of action with the Kurt Lewin model on 36 students, the results of the study showed a linear increase in the class average score from 64.44 (pretest) to 81.51 (cycle III). The percentage of classical completeness also increased significantly from 38.89% to 100.00% at the end of the cycle. The decrease in the standard deviation to 6.42 proves the reduction in the gap in understanding between students. It is concluded that the integration of PhET Simulation with the Discovery Learning model is effective in visualizing abstract concepts, encouraging independent exploration, and optimizing students' cognitive learning outcomes.